(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides a comprehensive overview of the legal frameworks and protections available for foreign direct investment (FDI). It explores the various international and domestic laws that govern FDI, emphasizing the importance of a stable legal environment for attracting and safeguarding investments. It outlines the rights and protections afforded to investors, such as protection against expropriation, guarantees of fair and equitable treatment, and dispute resolution mechanisms. The analysis also addresses the challenges investors might face, including regulatory changes, political risks, and enforcement issues. Relevant case studies that illustrate the practical implications of legal frameworks in various jurisdictions. This article serves as a crucial resource for understanding the legal landscape surrounding foreign direct investment and the measures in place to encourage and protect investors.